Evaluating socio-demographic, behavioral, and maternal factors in the dual burden of malnutrition among school-aged children in Batam, Indonesia - Erda, Roza; Hamidi, Dachriyanus; Desmawati, Desmawati; Rasyid, Rosfita; Sarfika, Rika (Narra J, 2025)
Malnutrition among school-aged children in urban-industrial settings presents a dual burden of undernutrition and overnutrition. The aim of this study was to examine factors influencing the nutritional status of elementary school children in Batam, Indonesia. A case-control study was conducted in Batam, focusing on children aged 6–12 years, with malnourished cases (undernutrition and overnutrition) and well-nourished controls, along with their mothers. Respondents were selected through stratified random sampling from public elementary schools. Inclusion criteria encompassed children enrolled in these schools, while exclusion criteria involved children with chronic health conditions. Data were collected via structured interviews utilizing validated questionnaires, anthropometric assessments (weight-for-age and height-for-age), and parent-reported socioeconomic, behavioral and family characteristics. Statistical analysis involved binary logistic regression to identify significant risk factors associated with malnutrition. A total of 188 children, including 94 malnourished cases (40 undernutrition and 54 overnutrition) and 94 well-nourished controls. The findings revealed significant differences between cases and controls in socioeconomic factors (pocket money (p=0.027), family income (p=0.042)), behavioral factors (sedentary activity (p=0.019), dietary habits (p=0.037)) and family factors (maternal BMI, p=0.011; maternal nutritional knowledge, p=0.004; parenting style, p=0.035). Dominant risk factors for malnutrition (undernutrition or overnutrition) included poor dietary habits (adjusted odds ratio (aOR): 0.451; 95%CI: 0.225–0.901; p=0.024), maternal obesity class II (aOR: 0.126; 95%CI: 0.030–0.535; p=0.005), and low maternal nutritional knowledge (aOR: 0.294; 95%CI: 0.124–0.696; p=0.005). Targeted family-centered interventions focusing on dietary practices and maternal education are therefore recommended to address this issue.